2015
DOI: 10.5144/0256-4947.2015.19
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of pediatric ulcerative colitis in Saudi Arabia: a multicenter national study

Abstract: BACKGROUNDDespite the extensive reporting of pediatric ulcerative colitis (UC) from industrialized developed countries, reports from developing countries are limited to small-case series from single centers. The objective of our large multicenter study was to determine the clinical, laboratory, endoscopic characteristics of UC in children from a developing country, Saudi Arabia.DESIGN AND SETTINGSA retrospective study of children diagnosed with UC under the age of 18 years during the period from 2003 to 2012.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
1
8
4
Order By: Relevance
“…The clinical presentation of UC patients in this study was similar to other studies were bloody diarrhea and abdominal pain are the most common presentations [2,9,11,14,16,17]. For instance, Al-Qabandi, et al [14] reported bloody diarrhea in 94% and abdominal pain in 78% of UC patients.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…The clinical presentation of UC patients in this study was similar to other studies were bloody diarrhea and abdominal pain are the most common presentations [2,9,11,14,16,17]. For instance, Al-Qabandi, et al [14] reported bloody diarrhea in 94% and abdominal pain in 78% of UC patients.…”
Section: Discussionsupporting
confidence: 73%
“…In our study, high ESR and CRP was noted in 51% and 57% respectively. This is lower than that reported in Saudi patients (82% and 63% respectively) [16]. Hypoalbuminemia was seen in 47% of patients in this study compared to that reported by AlSaleem, et al [16] which was 33%.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations